Innovation in Social Science - Casas Trujillo, Jennyfer Paola (Central European Journal of Educational Research, 2024)
Bibliography of the reviewed book: Márkus, E., Boros, J., & Kozma, T. (2022). Sustainability of innovation. Debrecen University Press